POLA KONSUMSI DAN STATUS OBESITAS PADA PEMANDU WISATA DI KABUPATEN BADUNG, PROPINSI BALI - Ni Komang Wiardani; A.A. Ngurah Kusumajaya (JURNAL NUTRISIA, 2018)
Tour guides working to serve foreign tourists are particularly vulnerable to obesity and non-communicable diseases. They are exposed every day to the lifestyle and diet of the western tourists who are served that tend to be high energy, fat and cholesterol. Lifestyle tour guides should follow the lifestyle of tourists who more activity and banquets, especially at night until the early hours which must also be followed by the tour guide.The study aims to determine the relationship of consumption pattern and obesity status on the tour guide. The study was conducted in Badung Bali Province with the goal of the research is the work Travel guide Travel agency foreign tourists. The samples were carried out by multistage random sampling, with a sample size of 109 people. Data collected from a sample identity, waist circumference, body mass index. Food consumption patterns include the number, type and frequency of consumption of foodstuffs with Semi quantitative method frequeny Food Questionnaire (SQ-FFQ). It showed the number of subjects as many as 109 people with 73.4% male and 26.6% female. About 21,1 % subject have over all obesity and 37,6% have central obesity. Food consumption patterns seen on the amount that exceeds the adequacy of that energy and fat 48.6%, protein 57.8%. The type of foods frequently consumed are chicken, eggs, shrimp, squid is a food consumed regularly >2 times a week. The analysis showed a significant correlation between the pattern of food consumption with obesity status (p <0.05) and exceeds consumption adequacy, have a higher risk of the obesity status than lower concumption (RP > 1,00 ; CI >1). The study showed a significant correlation between consumption pattern with obesity status tour guide in the district of Bali province Badung. Keywords: Consumption pattern, obesity status , tour guide